Molecular basis of crosstalk between oncogenic Ras and the master regulator of hematopoiesis GATA‐2. (23rd July 2014) - Katsumura, Koichi R; Yang, Chenxi; Boyer, Meghan E; Li, Lingjun; Bresnick, Emery H
Abstract: Disease mutations provide unique opportunities to decipher protein and cell function. Mutations in the master regulator of hematopoiesis GATA‐2 underlie an immunodeficiency associated with myelodysplastic syndrome and leukemia. We discovered that a GATA‐2 disease mutant (T354M) defective in chromatin binding was hyperphosphorylated by p38 mitogen‐activated protein kinase. p38 also induced multisite phosphorylation of wild‐type GATA‐2, which required a single phosphorylated residue (S192). Phosphorylation of GATA‐2, but not T354M, stimulated target gene expression. While crosstalk between oncogenic Ras and GATA‐2 has been implicated as an important axis in cancer biology, its mechanistic underpinnings are unclear. Oncogenic Ras enhanced S192‐dependent GATA‐2 phosphorylation, nuclear foci localization, and transcriptional activation. These studies define a mechanism that controls a key regulator of hematopoiesis and a dual mode of impairing GATA‐2‐dependent genetic networks: mutational disruption of chromatin occupancy yielding insufficient GATA‐2, and oncogenic Ras‐mediated amplification of GATA‐2 activity. Synopsis: This study shows that p38α increases GATA‐2 activity at endogenous target genes by inducing GATA‐2 multi‐site phosphorylation. Oncogenic Ras is found to amplify this mechanism, which provides a potential molecular explanation for the cooperative promotion of cancer development by Ras and GATA‐2. p38α promotes multi‐site GATA‐2 phosphorylation, increasing its localization in nuclear foci enriched in an active form of RNA polymerase II and its capacity to regulate endogenous target genes. A single serine residue within GATA‐2, Ser192, mediates p38α‐dependent multisite phosphorylation and enhanced GATA‐2 activity. Oncogenic Ras amplifies p38α‐ and Ser192‐dependent GATA‐2 multi‐site phosphorylation and function, thus providing a framework for understanding Ras–GATA‐2 interactions in the development and progression of cancer. Abstract : This study shows that p38α increases GATA‐2 activity at endogenous target genes by inducing GATA‐2 multi‐site phosphorylation. Oncogenic Ras is found to amplify this mechanism, which provides a potential molecular explanation for the cooperative promotion of cancer development by Ras and GATA‐2.